2014
DOI: 10.1186/1476-4598-13-243
|View full text |Cite
|
Sign up to set email alerts
|

Human epididymis protein 4 in association with Annexin II promotes invasion and metastasis of ovarian cancer cells

Abstract: BackgroundThe objective of the present study was to identify human epididymis protein 4 (HE4) interacting proteins and explore the mechanisms underlying their effect on ovarian cancer cell invasion and metastasis.MethodsHE4 interacting proteins were identified by mass spectrometry and validated by co-immunoprecipitation and pull-down assays. The scratch test, the Transwell assay and animal experiments were used to assess the invasive and metastatic abilities of ovarian cancer cells before and after transfectio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
48
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 49 publications
(49 citation statements)
references
References 19 publications
1
48
0
Order By: Relevance
“…Inclusion of preoperative serum HE4 levels into the diagnostic Risk of Ovarian Malignancy Algorithm (ROMA) results in demonstrably improved specificity and sensitivity in detection and monitoring of the disease over Cancer Antigen 125 (CA 125), pelvic sonography, and menopausal status alone [5]. Research has also shown its ability to support EOC pathogenesis, including the promotion of proliferation, chemoresistance, antiestrogen resistance, adhesion, invasion, and migration [6][7][8][9][10][11][12][13][14][15][16][17]. One oncogenic pathway that has consistently been shown to interact with HE4 in several studies is the extracellular signal regulated kinase (ERK) pathway.…”
Section: Introductionmentioning
confidence: 99%
“…Inclusion of preoperative serum HE4 levels into the diagnostic Risk of Ovarian Malignancy Algorithm (ROMA) results in demonstrably improved specificity and sensitivity in detection and monitoring of the disease over Cancer Antigen 125 (CA 125), pelvic sonography, and menopausal status alone [5]. Research has also shown its ability to support EOC pathogenesis, including the promotion of proliferation, chemoresistance, antiestrogen resistance, adhesion, invasion, and migration [6][7][8][9][10][11][12][13][14][15][16][17]. One oncogenic pathway that has consistently been shown to interact with HE4 in several studies is the extracellular signal regulated kinase (ERK) pathway.…”
Section: Introductionmentioning
confidence: 99%
“…In our study using recombinant mouse WFDC2, we were unable to identify any proteinase inhibitory activity nor were we able to show robust antimicrobial activity against a number of bacteria. Other studies, largely from the cancer field, have shown that WFDC2 has the capacity to promote cell growth [43][44][45][46][47][48].…”
Section: Discussionmentioning
confidence: 99%
“…was identi ed as a robust interacting partner of HE4 by mass spectrometry and co-immunoprecipitation, the HE4-ANXA2 complex can promote ovarian cancer cell invasion and migration in vitro and tumor distant metastasis of lung in vivo, downregulation of HE4 decreases expression of MKNK2 and LAMB2, which were associated with signaling pathways of MAPK and focal adhesion [5].…”
Section: Discussionmentioning
confidence: 99%
“…In physiological conditions, HE4 is secreted into the blood to act as a protease inhibitor and is involved in the maturation of sperm cells [2]. Several types of cancers are associated with HE4 overexpression both in serum and tissues, and it is a relatively promising and useful biomarker for the diagnosis of ovarian cancer [3][4][5], primary fallopian tube carcinoma [6], endometrial cancer(combined with CA125) [7], lung cancer [8], breast cancer(combined with miR-127) [9], gastric cancer [1], colorectal cancer [10] and pancreatic adenocarcinomas [11]. In 2008, HE4 was cleared as a serum marker to monitor disease recurrence or progression in patients with epithelial ovarian cancer (EOC) by Food and Drug Administration of USA.…”
Section: Introductionmentioning
confidence: 99%